MULTIMEDIA MICROLEARNING CREATION TRAINING SMP IT ATTIN WEST SUMATERA - Liza Yulia Sari; vivi fitriani; Diana Susanti; Wira Solina (Universitas PGRI Sumatera Barat, 2023)
Microlearning is small-scale learning containing content designed into small segments through various media formats, so that the available information becomes